Peningkatan Literasi Sistem Pelayanan Kesehatan pada Remaja SMA sebagai Upaya Meningkatkan Akses dan Pemanfaatan Layanan Kesehatan Reproduksi - Paramita Boni Lestari; Fariz Kahendra; Kristoforus Marselinus; Diva Noviyanti; Tasya Amalia (Jurnal Kemitraan Masyarakat, 2026)
Adolescents are a population group vulnerable to various reproductive health issues, making adequate knowledge essential for developing positive health behaviors. However, access to accurate reproductive health information remains limited. This community service program aimed to improve students' knowledge of reproductive health through educational activities. The program was conducted on May 29, 2026, at Senior High School X, involving 100 students through the stages of situation analysis, planning, implementation, and evaluation. The intervention was delivered using lectures and interactive discussions, while the evaluation employed a pre-test and post-test design consisting of 10 questions. The results showed that 92% of students had previously received reproductive health information, primarily from the internet. Before the intervention, 42% of students had good knowledge, 54% had moderate knowledge, and 4% had poor knowledge. After the educational intervention, the proportion of students with good knowledge increased to 91%, while the proportions with moderate and poor knowledge decreased to 8% and 1%, respectively. Reproductive health education proved effective in improving students' knowledge and should therefore be implemented continuously by involving schools and healthcare professionals.